A case study of superintendent leadership behaviors: bridging the transition between a new and long-serving superintendent - Farley, Daniel (Kansas State University, 2024)
The purpose of this study is to examine the transition in a rural Midwestern school district from a long-serving superintendent who served sixteen years in the position to a recently hired superintendent, focusing on leadership behaviors and how the observed behaviors of the two superintendents influenced the transition period between superintendent tenures. The theoretical framework guiding this study was Roger’s “Diffusion of Innovations” theory. The investigation uses a mixed methods convergent design to conduct a case study of the superintendent leadership transition utilizing three forms of data collection: The Leadership Behavior Description Questionnaire (LBDQ), interviews, and observations at the selected site. The significance of this study is its potential to identify leadership behaviors that can be used to better understand how an incoming superintendent responds during the transition period in a rural school district after the retirement of a long-serving superintendent. The findings from the study demonstrated the outgoing and incoming superintendent utilized qualities from four selected leadership frameworks (i.e., transformation, distributive, servant, and adaptive). The behaviors of the superintendents did affect the transition and there was a stronger alignment between incoming superintendent stakeholder responses than the outgoing superintendent stakeholder responses. Recommendations for future research and implications for practice are detailed from the findings of the study and discussed in connection with the theoretical framework.
Keywords: Superintendent; Transition; Leadership framework; Behavior